Relative Prices and Climate Policy: How the Scarcity of Non-Market Goods Drives Policy Evaluation - Moritz A. Drupp; Martin C. Hänsel (Center for Economic Studies and ifo Institute (CESifo), 2020)
Climate change not only impacts production and market consumption, but also the relative scarcity of non-market goods, such as environmental amenities. We study fundamental drivers of the resulting relative price changes, their potential magnitude, and their implications for climate policy in Nordhaus' prominent DICE model, thereby addressing one of its key criticisms. We propose plausible ranges for these relative prices changes based on best available evidence. Our central calibration reveals that accounting for relative prices is equivalent to decreasing pure time preference by 0.6 percentage points and leads to a more than 50 percent higher social cost of carbon.
Keywords: Q01; Q54; H43; D61; D90; 330; climate policy; discounting; non-market goods; social cost of carbon; substitutability